A Portrait Bust of Julia Mamaea from the Pantanello of Hadrian’s Villa? (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2025)
This paper examines the reported discovery of a «bust of Julia Soaemias» during the eighteenth-century excavations conducted by Francesco Antonio Lolli in the Pantanello area of Hadrian’s Villa (Tivoli), proposing its identification with a portrait of Julia Mamaea now in Potsdam, at Schloss Sanssouci. A combined analysis of antiquarian sources and collecting history makes it possible to reconstruct the sculpture’s transfer from Cardinal Polignac’s collection to the Brandenburg holdings of Frederick II of Prussia, offering substantial evidence for its Tiburtine provenance. The identification adds a significant piece to the sequence of imperial portraits from the Villa and illuminates the role of the Severan dynasty in the continued use of the complex well into the third century.
Keywords: Hadrian’s Villa; Julia Mamaea; Pantanello; Polignac; Roman portraiture